2007
DOI: 10.3133/of2007-1047.srp034
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Cooper Bay Dislocation Zone (CBDZ) represents a major NW-SE trending tectonic boundary within the island of South Georgia that juxtaposes components of a Middle Jurassic to mid-Cretaceous island-arc and back-arcbasin system. New detailed structural data from the southern end of the dislocation zone reveal that earliest displacement along the boundary appears to have been associated with dip-slip reverse shear, characterised by widespread proto-to meso-mylonitic granitic rocks within the basement assemblage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Drygalski Fjord and Larsen Harbour complexes were tectonically emplaced along the Cooper Bay Shear Zone, a NW-trending mylonitized fault zone with a complicated history of normal, reverse, oblique and left-lateral strike-slip or transtensional deformation (Storey and Macdonald, 1984;Curtis, 2007;Curtis et al, 2010). Dalziel (1981) suggested that some of these movements occurred in mid-Cretaceous times on the basis of observations on rocks in South America that he assumed to be near neighbours to South Georgia's.…”
Section: Deformation and Ophiolite Emplacementmentioning
confidence: 99%
“…The Drygalski Fjord and Larsen Harbour complexes were tectonically emplaced along the Cooper Bay Shear Zone, a NW-trending mylonitized fault zone with a complicated history of normal, reverse, oblique and left-lateral strike-slip or transtensional deformation (Storey and Macdonald, 1984;Curtis, 2007;Curtis et al, 2010). Dalziel (1981) suggested that some of these movements occurred in mid-Cretaceous times on the basis of observations on rocks in South America that he assumed to be near neighbours to South Georgia's.…”
Section: Deformation and Ophiolite Emplacementmentioning
confidence: 99%